2020 Clinical practice guidelines for Bradyarrhythmias and conduction disorders - A. Sh. Revishvili; E. A. Artyukhina; M. G. Glezer; V. A. Bazaev; R. E. Batalov; L. A. Bokeria; O. L. Bokeria; K. V. Davtyan; E. A. Ivanitsky; A. S. Kovalev; S. N. Krivolapov; D. S. Lebedev; et al. (Российский кардиологический журнал, 2021)
Endorsed by: Research and Practical Council of the Ministry of Health of the Russian Federation.